Patterning of light-emitting conjugated polymer nanofibres - Francesca Di Benedetto; Andrea Camposeo; Stefano Pagliara; Elisa Mele; Luana Persano; Ripalta Stabile; Roberto Cingolani; Dario Pisignano (2008)
Organic materials have revolutionized optoelectronics by their processability, flexibility and low cost, with application to light-emitting devices for full-colour screens1, solar cells2 and lasers3, 4. Some low-dimensional organic semiconductor structures exhibit properties resembling those of inorganics, such as polarized emission5 and enhanced electroluminescence6. One-dimensional metallic, III–V and II–VI nanostructures have also been the subject of intense investigation7, 8 as building blocks for nanoelectronics and photonics. Given that one-dimensional polymer nanostructures, such as polymer nanofibres, are compatible with sub-micrometre patterning capability9 and electromagnetic confinement within subwavelength volumes8, they can offer the benefits of organic light sources to nanoscale optics. Here we report on the optical properties of fully conjugated, electrospun polymer nanofibres. We assess their waveguiding performance and emission tuneability in the whole visible range. We demonstrate the enhancement of the fibre forward emission through imprinting periodic nanostructures using room-temperature nanoimprint lithography, and investigate the angular dispersion of differently polarized emitted light.